Resistencia a la tracción de postes de fibra de vidrio con cemento autoadhesivo instrumentado a diferentes calibres con sistema rotatorio protaper - Sánchez Varela, Galo Iván (2017)
The main objective of the present work was to determine the tensile strength required to measure the point at which dislocation of cemented glass fiber poles occurs through a dual polymerization cement to different endodontically treated root canal sizes, Our case with Protaper rotary system. The tests were performed using the MTS brand universal testing machine which pulled the posts at a speed of 1mm per minute. Until recently, it was believed that fiberglass posts reinforced the teeth treated by endodontics, however, this belief is currently discarded since any element foreign to the natural dental tissues tends to weaken its structure. The main and determining factor influencing the maintenance of the fiberglass post inside the root canal will be the retention capacity of the post…